Use of Interactive Media In Biochemical Material - Puji Kurniawati; Reni Banowati Istiningrum (IJCER (International Journal of Chemistry Education Research), 2017)
ABSTRACT: A study of the use of interactive media in Biochemistry materials at Chemical Analysis Department, Islamic University of Indonesia has been done. Interactive media used in this research is animation media based on molymod and Flash. Molymod is used in lecturing activities to explain the macromolecular bonds and structures that are the focus of the Biochemistry course while the Flash-based animation is expected to improve students' understanding of biochemical metabolism processes in the body. The purpose of this study is to increase students' interest in biochemical learning which is known to be difficult and unattractive.Stages of this research there are 6, namely the initial stage, pre-design, design, model evaluation, field application and evaluation of results. The initial stage is done by improving the Course Outline (CO) and Teaching Unit Course (SAP) as well as the creation of lecture modules. Contents, materials and display modules have been reviewed by incorporating elements of analysis of biochemical examples that are often performed in the industrial world. Molymods of small capacity per set can only make two interconnected monomers. Flash-based animation media can be used during college or can be opened by students independently. The use of interactive media can stimulate students' high interest and understanding, ie 74.38% and 72.88% respectively. The correlation relationship between understanding and interest is also high which is marked with correlation coefficient value 0.806. The achievement of value â‰¥ B / C obtained with interactive media equal to 76,57% and Lecturer Performance Value (NKD) equal to 3,56.Keywords:Â interactive media, molymod, biochemistryReceived: 22 June 2017, Revised: 13 August 2017, 1 September 2017